Evaluation of Speech Intelligibility And Factors Influencing Its Outcome in Patients with Tongue Reconstruction Using Radial Forearm Free Flap - Malik, Sakina; Sarwar, Saad Ur Rehman; Rashid, Mamoon; Khan, Muhammad Ibrahim; Qureshi, Mehreen Masud; Khan, Hala (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the speech outcomes in patients undergoing tongue reconstruction after tumour resection in terms of intelligibility and to examine the factors influencing the outcome. Study Design: Prospective observational study. Place and Duration of Study: Department of Plastic Surgery, Shifa International Hospital, Islamabad, Jan 2015 to Jan 2020. Methodology: A total of 109 patients diagnosed with tongue cancer meeting the inclusion criteria were included in the study. All the participants underwent tumor resection followed by adjuvant radiotherapy (unless refused by the patients). Patients were followed for six months and then underwent speech evaluation via the Functional Intra-oral Glasgow Scale score and Likert scale. Results: Thirty (27.5%) patients could be clearly understood at all the times, while 27 (24.8%) and 42 (38.5%) required some and frequent repetition, respectively. Nine (8.3%) patients could only be understood by close relations and one patient was completely unintelligible. Advancing age (p=0.01), male gender (p=0.01), tumour stage (p=0.004), presence of comorbidities (p=0.004) and degree of resection (p=0.004) had a significant statistical relationship with speech outcome. Addiction (p=0.32), adjuvant radiotherapy (p=0.97) and the development of complications (p=0.59) had no effect on speech. Conclusion: The provision of a mobile reconstructed tongue gives speech intelligibility in a majority of the patients however, the degree of speech recovery is directly dependent on advanced age, disease stage, the presence of comorbidities and degree of resection.